Formation and Characterization of Crystalline Hydroxyapatite Coating with the (002) Texture; IOP Conference Series: Materials Science and Engineering; Vol. 116 : Advanced Materials and New Technologies in Modern Materials Science - Grubova I. Yu. Irina Yurievna; Priamushko T.; Chudinova E. A. Ekaterina Aleksandrovna; Surmeneva M. A. Maria Alexandrovna; Korneva O. Yu. Olga Yurievna; Epple M.; Prymak O.; Shulepov I. A. Ivan Anisimovich; Surmenev R. A. Roman Anatolievich (2016, 2016)
Title screen